2010
DOI: 10.5997/sposun.20.119
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Employment Situations of University Athletic Clubs Based on Differences in Instruction and Management: A Case Study of Wrestlers

Abstract: Regarding sports as an industry, it is indispensable that top athletes become role models and icons. However, a great deal of change has been occurring in the career environment after graduation for the athletes of Japan. They have anxieties about their career possibilities and this is a major problem for developing the sports industry. This study investigated male students who belonged to university wrestling clubs. A survey about employment rates was conducted at five universities. The results showed a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This research will conduct a longitudinal study over a long period to examine the following 2 objectives:ˆrst, to identify the changes in the level of LS acquisition through university sports over a 4 year university period, and second, to identify the time Shimizu et al (2010) recommend that a speciˆc sport be chosen for studying the academic careers or employment of athletes as the environment surrounding the athletes will diŠer according to the type of sport and the level of competition. In this research, men's wrestling was chosen.…”
Section: The Issue and Objectivesmentioning
confidence: 99%
“…This research will conduct a longitudinal study over a long period to examine the following 2 objectives:ˆrst, to identify the changes in the level of LS acquisition through university sports over a 4 year university period, and second, to identify the time Shimizu et al (2010) recommend that a speciˆc sport be chosen for studying the academic careers or employment of athletes as the environment surrounding the athletes will diŠer according to the type of sport and the level of competition. In this research, men's wrestling was chosen.…”
Section: The Issue and Objectivesmentioning
confidence: 99%
“…Many athletes cannot even job hunt as they are frequently unavailable due to their daily training, camps, and overseas competitions. Shimizu et al (2010), for example, have compared the employment rates of top level college student athletes (speciˆcally, wrestlers) and of other students, and reported that the employment rate upon graduation is higher for the non-athlete group (wrestlers 57.0z, non-athletes 65.5z).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that time constraints due to training and other factors make it difficult for top-level college athletes to perform well academically and to find jobs. This makes it difficult for them to find a career without difficulties after their retirement from competitions (Shimizu, Takahashi, & Kono, 2010).…”
Section: Jwf Athlete Pathway Development Projectmentioning
confidence: 99%